1993
DOI: 10.1093/jnci/85.15.1235
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cytosine DNA-Methyltransferase Activity During Colon Cancer Progression

Abstract: Further studies are needed to determine whether this abnormal methylation capacity plays a role in establishing the abnormal DNA methylation patterns seen in human malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
166
2
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(180 citation statements)
references
References 0 publications
11
166
2
1
Order By: Relevance
“…21 Our results of elevated DNA methyltransferase levels in leukaemia are similar to studies in colon cancer that have used quantitative RT-PCR assays, where an average of 3.7-fold 23 and 2.6-fold 24 increases in DNA MTase transcripts were reported when normalised with GAPDH. Lee et al 24 also found that the level of DNA MTase expression in colon cancer was 1.8-fold higher when normalised to actin, however, no significant elevation was detected when normalised to histone H4.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…21 Our results of elevated DNA methyltransferase levels in leukaemia are similar to studies in colon cancer that have used quantitative RT-PCR assays, where an average of 3.7-fold 23 and 2.6-fold 24 increases in DNA MTase transcripts were reported when normalised with GAPDH. Lee et al 24 also found that the level of DNA MTase expression in colon cancer was 1.8-fold higher when normalised to actin, however, no significant elevation was detected when normalised to histone H4.…”
Section: Discussionsupporting
confidence: 85%
“…DNA MTase expression has been assayed previously in lung, liver and colon tumour samples using a wide range of methods, including protein-based assays 21,22 and RNA-based assays 20,[22][23][24]37 and the results obtained have been variable. However, in this study we developed a standardised competitive RT-PCR assay which enabled accurate measurement of DNA MTase mRNA expression within and between samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It involves distinctly ordered alterations in common oncogenes and tumour-suppressor genes (Hamilton, 1992). Genomic hypomethylation is a special feature of colorectal cancer occurring at an early stage of the disease (Goelz et al, 1985;Feinberg et al, 1988), although regional hypermethylation (Issa et al, 1994;Hiltunen et al, 1997) and increased activity of DNA methyltransferase (Issa et al, 1993) have also been reported with progression of the tumour.…”
Section: Discussionmentioning
confidence: 99%
“…Cell biology assays DNMT activity was determined as previously described (Issa et al, 1993), and normalized to protein levels. Anchorageindependent growth assays, including suspension culture, were performed as previously described (Zhang et al, 2003).…”
Section: Reporter Plasmidsmentioning
confidence: 99%